Transurethral ureteric embolization for locally advanced cervical cancer with uretero-vaginal fistula – A case report. (March 2023) - Acton, H.; Motyer, R.; O'Mahony, J.; Brennan, I.; Ryan, J.M.
Abstract: Introduction: Targeted radiotherapy, surgery, and localised disease progression can all result in fistulous tract formation in patients with a pelvic malignancy, in particular cervical or endometrial cancer. This report discusses a novel technique for palliative management of ureterovaginal fistulas in end-stage disease. Presentation of case report: We report the case of a 37 year old female with metastatic cervical squamous cell carcinoma previously treated with chemoradiation who presented with progressive disease and secondary development of a symptomatic ureterovaginal fistula. Discussion: This case report discusses the causes and sequalae of uretero-vaginal fistula formation, the role of the interventional radiology with regards to palliative intervention, and potential patient factors that can affect performance of such procedures. Conclusion: Interventional radiology plays an important role in palliative and symptomatic management of end stage malignant disease. Ureteric embolisation via a retrograde transurethral approach by way of an existing stent is a novel approach to access making the procedure easier for both the patient and radiologist. Highlights: Fistula formation is a common complication of advanced pelvic malignancy. Radiological intervention is an important consideration when managing patient symptoms. Utilisation of existing devices and patient positioning should be considered to improve the success of the procedure.